Beta-carotene encapsulated in food protein nanoparticles reduces peroxyl radical oxidation in Caco-2 cells. (January 2015) - Yi, Jiang; Lam, Tina I.; Yokoyama, Wallace; Cheng, Luisa W.; Zhong, Fang
Abstract: Beta-carotene (BC) was encapsulated by sodium caseinate (SC), whey protein isolate (WPI), and soybean protein isolate (SPI) by the homogenization-evaporation method forming nanoparticles of 78, 90 and 370 nm diameter. Indices of the chemical antioxidant assays, the reducing power, DPPH radical scavenging activity, and the hydroxyl radical scavenging activity (OH) were improved by nanoencapsulation, compared to free BC. Caco-2 cells were treated with dichlorofluorescin diacetate (DCFH-DA) to determine the cellular antioxidant activity (CAA) of BC. CAA of SC, WPI, and SPI nanoparticles was higher (60%) compared to BC alone (45%). FTIR-ATR showed the presence of BC in the nanoparticle preparations. XRD and DSC analyses suggested that BC is amorphous in the nanoparticles. BC encapsulated by WPI had the most advantageous release properties. Release was low with pepsin but high with trypsin suggesting that WPI might be the best protein delivery vehicle to deliver BC to the intestine. Graphical abstract: Highlights: FTIR–ATR results showed that the BC may be bonded to proteins through H-bonding. XRD and DSC analysis suggested that BC is amorphous in the delivery system. The chemical antioxidant activity of BC was improved by nano-encapsulation. Cellular antioxidant activity of three BC nano-particles was also improved.